Assessment of patient knowledge of diabetic goals, self-reported medication adherence, and goal attainment - Joli D. Fermo (Pharmacy Practice, 2006)
Background: Medication adherence is an integralaspect of disease state management for patientswith chronic illnesses, including diabetes mellitus. Ithas been hypothesized that patients with diabeteswho have poor medication adherence may haveless knowledge of overall therapeutic goals andmay be less likely to attain these goals.Objective: The purpose of this study was to assessself-reported medication adherence, knowledge oftherapeutic goals (hemoglobin A1C [A1C], lowdensity lipoprotein cholesterol [LDL-C] and bloodpressure [BP]), and goal attainment in adult patientswith diabetes.Methods: A survey was created to assessmedication adherence, knowledge of therapeuticgoals, and goal attainment for adult patients withdiabetes followed at an internal medicine or a familymedicine clinic. Surveys were self-administeredprior to office visits. Additional data were collectedfrom the electronic medical record. Statisticalanalysis was performed.Results: A total of 149 patients were enrolled.Knowledge of therapeutic goals was reported by14%, 34%, and 18% of survived patients for LDL-C,BP, and A1C, respectively. Forty-six percent, 37%,and 40% of patients achieved LDL-C, BP, and A1Cgoals, respectively. Low prescribing of cholesterolloweringmedications was an interesting secondaryfinding; 36% of patients not at LDL-C goal had notbeen prescribed a medication targeted to lowercholesterol. Forty-eight percent of patients weremedication non-adherent; most frequently reportedreasons for non-adherence were forgot (34%) andtoo expensive (14%). Patients at A1C goal weremore adherent than patients not at goal (p=0.025).Conclusion: The majority did not reach goals andwere unknowledgeable of goals; however, mostwere provided prescriptions to treat theseparameters. Goal parameters should be revisitedoften amongst multidisciplinary team members withfrequent and open communications. Additionally, it is imperative that practitioners discuss theimportance of medication adherence with everypatient at every visit.